Influence of type and concentration of sugars, supplemented with 8-hydroxyquinoline sulphate, on the vase life of waxflower - Dung, C.; Seaton, K.; Singh, Zora (Polskie Towarzystwo Nauk Ogrodniczych, 2017)
A study was conducted to test the effect of 58.5 mM maltose, glucose, fructose, galactose and sucrose, and sucrose concentrations of 14.6, 29.2, 58.5 and 117.0 mM supplemented with 200 mg L-1 8-hydroxyquinoline sulphate (HQS) on the vase life and stem fresh weight changes in waxflower (Chamelaucium Desf.). The effect of the interaction between sucrose and HQS concentrations on the vase life of the cultivar ‘Alba’ was also investigated. All the types of exogenous sugar significantly increased the vase life of flowers, but decreased the vase life of leaves of waxflower cultivars compared with the deionized water controls, except the leaves of ‘Lady Stephanie’, ‘Purple Pride’ and ‘Mullering Brook’. The flower vase life of almost all the cultivars treated with sucrose was not significantly different from the life of the cultivars kept in fructose and glucose, except ‘Laura Mae Pearl’, whose flower vase life in sucrose was significantly lower (9.7%) than in fructose. By contrast, the vase life of flowers of the cultivars treated with sucrose was longer than of those in maltose and galactose. At sucrose concentrations of up to 117.0 mM coupled with 200 mg L-1 HQS, the flower vase life of six out of eight cultivars significantly increased, except in ‘Laura Mae Pearl’ and ‘Mullering Brook’, whose flower vase life was maximized at the concentrations of 29.2 and 58.5 mM respectively, while the vase life of their leaves decreased. Sucrose concentrations from 14.6 to 29.2 mM coupled with 50 mg L-1 HQS maximized vase life for both the flowers and leaves of ‘Alba’. Cultivars with a longer vase life of flowers maintained stem fresh weight above the initial stem fresh weight longer.